Contribution of Islamic Sharia to Eliminating Corruption Culture (UIN Syarif Hidayatullah Jakarta, 2023)
Islamic Sharia contains principles that help overcome and minimize a culture of corruption, especially in a Muslim-majority country like Indonesia. Given that corruption can directly or indirectly have a negative impact on all aspects of life, it is essential to eliminate and reduce the culture of corruption in society. The method used in this study is a qualitative research method with a literature approach. The results of the study state that Sharia law has made a significant contribution to eradicating the culture of corruption that is rampant in society. Honesty, integrity and accountability are just a few of the anti-corruption concepts in Islamic law that can form the basis of government or business initiatives to eradicate corrupt practices. In addition, alms, zakat, and pilgrimage can also help increase public awareness of good deeds and positively impact eradicating corruption. Keywords: Islamic Sharia; Contribution; Corruption Culture